F. M. Dostoevsky – great human-lover, expert in human, well-wisher of human, sage and visionary - Babosov, Evgenii M. (Journal of the Belarusian State University. Sociology, 2021)
The philosophical meaning and humanistic pathos of F. M. Dostoevsky’s work is revealed, embodied in his novels and «The diary of a writer». The depth and bottomlessness of a person – the writer’s symbol of faith – are presented. The philosophical, ethical and psychological generalisations of the Russian writer are presented as the central point of the metaphysical problem of man as a personality, her life, quest, suffering, love, faith. The theory of F. M. Dostoevsky’s creativity is reconstructed, for which a person is interesting when he embarks on only his own, individual path, but passing which, highlights something typical for the entire people, its historical fate and destiny, strength and weakness. Only in the personal identity of each person is the general identity of the nation embodied; to defend in any circumstances the honour of the Russian man and the honour of his people – this is precisely what the citizen writer saw as the vocation of Russia. The dialectic of love, freedom, beauty and immortality as components of the meaning of human life is revealed. Against this background, death is presented as an inevitable moral lesson, the meaning of which is to sharpen the feelings of love and humility: love for man and humility before God. This understanding of life and death is opposed by demonic, a phenomenon devoid of love and humility. For F. M. Dostoevsky, who had an acute presentiment of future social upheavals in Russia and Europe, devilry is embodied in the revolutionary ideas of seizing power, restructuring society and man according to the patterns of political leaders who only yearn for domination and submission of others to their will. The prophecies and premonitions made by F. M. Dostoevsky about the future of Russia and its place in world history are characterised. The emphasis is on the writer’s rejection of the revolution as a fratricidal war and the denial of the viability of communist ideas and ideals. Only religiously coloured humanism can be opposed to these gloomy forecasts: a better future will come when people, based on the implementation of the main Christian thesis, to love their neighbour as themselves, will be able to unite into a single harmonious whole or the paradise of Christ.